Best Answer

Set up the equation and solve:

13 = 7 + s (next subtract 7 from each side of the equation to solve for s)

6 = s

Q: 13 equals 7 plus s s equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Related questions

13 = 7 + s(13 - 7) = (7-7) + s6 = s

no it;s not the answer is 2

Doc, Happy, Grumpy, Sleepy, Bashful, Sneezy and Dopey equal[s] the 7 dwarves.

7z + 6s + s = 7z + 7s This can then be factorised using 7 as the factor: 7z + 7s = 7(z + s)

the x's are -7's

s = 7, t = -3

9s + 7 = -11 9s = -18 s = -18/9 s = -2

-1

7+7+7+7+7+7+7/7=43 7 times 6=42 plus 1 whole=43

s would be the variable in this equation and after calculating it would be 6/7

4

s = -70